2017
DOI: 10.21817/ijet/2017/v9i2/170902051
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Electro Discharge Machining of Holes and Grooves: AnAssessment of Process Parameters

Abstract: Abstract-The need for a better cooling purpose in bio medical, electronics, microprocessors and radars has attracted many researchers. Since, microchannels fulfil this objective it's machining through different micro machining techniques requires more skill and knowledge. Micro electrical discharge machining (EDM)is considered as one of the advanced methods of machining micro tools, dies, channels, grooves etc. More emphasis should be given to this machining process so that complicated geometries with least ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…An increase in discharge current leads to a direct increase in the discharge energy of the pulse. Several researchers have found that increasing the discharge current leads to an increase in overall MRR of the workpiece, however it also leads to an increase in the electrode wear rate (EWR) and overcut of the machined feature [71,77,78]. Higher discharge current also interferes with the shape of the machined geometric feature, i.e.…”
Section: Electrical Parametersmentioning
confidence: 99%
“…An increase in discharge current leads to a direct increase in the discharge energy of the pulse. Several researchers have found that increasing the discharge current leads to an increase in overall MRR of the workpiece, however it also leads to an increase in the electrode wear rate (EWR) and overcut of the machined feature [71,77,78]. Higher discharge current also interferes with the shape of the machined geometric feature, i.e.…”
Section: Electrical Parametersmentioning
confidence: 99%